Sociodemographic differences associated to caries experience and prevalence among users of a public health network - Corchuelo-Ojeda, Jairo (Revista Facultad de Odontología Universidad de Antioquia, 2012)
Introduction: dental caries has been considered a public health problem; the latest national studies have shown some reduction in caries prevalence, but in unequal way and in some regions only. This study explores caries experience and its possible connections to social factors and oral health practices of users of dental services in 40 institutions of the Red Pública Departamental (state-based public health net) in Valle del Cauca, Colombia. Methods: this was a cross-sectional analytic study on 1.566 users; both traditional and modified DMFT (decayed, missing and filled teeth) indexes were registered, as well as caries experience, caries prevalence and DMFT levels. The participants filled out a structured questionnaire which included sociodemographic variables and oral health practices. The estimators were calculated following the proposed design and using the statistical program SPSS®, version 17, and Epi 3.5.1. Results: caries experience did not show significant differences by sex, and it was observed with a greater proportion among males than among females between twelve and twenty-five years of age. Concerning ype of social security coverage, the patients with smaller amounts of caries experience were the ones covered by the contributive regime —although after the age of 34 all of them already presented caries experience—. The percentage of caries prevalence found was 64.3% (CI 95%: 62-66%). Conclusions: both caries experience and caries prevalence were associated to age, social security coverage, and belonging to vulnerable population groups.